HPV16 E7 expression in skin induces TSLP secretion, type 2 ILC infiltration and atopic dermatitis‐like lesions. Issue 6 (20th January 2015) - Bergot, Anne‐Sophie; Monnet, Nastasia; Le Tran, Son; Mittal, Deepak; Al‐Kouba, Jane; Steptoe, Raymond J; Grimbaldeston, Michele A; Frazer, Ian H; Wells, James W
Abstract : Atopic dermatitis is a common pruritic and inflammatory skin disorder with unknown etiology. Most commonly occurring during early childhood, atopic dermatitis is associated with eczematous lesions and lichenification, in which the epidermis becomes hypertrophied resulting in thickening of the skin. In this study, we report an atopic dermatitis‐like pathophysiology results in a murine model following the expression of the high‐risk human papillomavirus (HPV) 16 oncoprotein E7 in keratinocytes under the keratin 14 promoter. We show that HPV16 E7 expression in the skin is associated with skin thickening, acanthosis and light spongiosis. Locally, HPV16 E7‐expressing skin secreted high levels of thymic stromal lymphopoietin (TSLP) and contained increased numbers of innate lymphoid cells (ILCs). High levels of circulating immunoglobulin E were associated with increased susceptibility to skin allergy in a model of cutaneous challenge, and to airway bronchiolar inflammation, enhanced airway goblet cell metaplasia and mucus production in a model of atopic march. Surprisingly, skin pathology occurred independently of T cells and mast cells. Thus, our findings suggest that the expression of a single HPV oncogene in the skin can drive the onset of atopic dermatitis‐like pathology through the induction of TSLP and type 2 ILC infiltration.